Cooperative competition: Business culture in the Finnish merchant community in the first half of the nineteenth-century: Business Culture in the Finnish Merchant Community in the First Half of the 19th Century. Issue 3 (27th May 2019) - Keskinen, Jarkko
Abstract : This article focuses on the collision between the communal-based and individual-based business cultures within the merchant community of Pori. The conflict is analysed by examining divergent petitions, complaints, and statement letters written to and by various authorities at the local, provincial, and national levels during the first half of the 19th century. The case study concentrates on confrontations between a nobleman of Swedish origin, Frans Fredrik Wallenstråle (1771–1857), and members of the local merchant community. The article strives to explain how and why the merchant community and the members of the town council made every possible effort to prevent Wallenstråle from developing his business activities and participating in communal cooperation within the community. In contrast to earlier literature, this article does not concentrate on petitions, their rhetoric, or the interaction between individual and state authorities. It analyses petitions as historical sources that resulted from collisions between the communal, cooperative business culture and vested interests.